ANATOLY I. KITOV: PERSONALITY THROUGH THE PRISM OF DOCUMENTS - Vladimir A. Kitov; Valery V. Shilov (Статистика и экономика, 2016)
The paper for the first time discusses nine formal characteristics and certifications of the outstanding Russian scientist Anatoly Ivanovich Kitov related to the military and the first postwar years (1944–1950). Their analysis allows detecting the manifestations of the properties of the personality and character of the young combat officer, and then of a student of the military Academy, which later became the basis of his scientific achievements, but also determined the conflict with the administrative-command system.